Analisis Laporan Keuangan Pada Ud Bandari Wayame Di Ambon - Firdayanti Rumew; Agus Siahaya; Sherly Evabioni Latuamury (Politeknik Negeri Ambon, 2015)
Research goal is to analize the financial performance at UD. Bandari trough the analysis the trend of the index. Purpose of trend analysis techniques to analyze the index is increased or decreased financial statements from one period to the next periodbut calculated over other years, with the expressed in a percentage.Model of research is through field research, ie research that directly conduct interviews with the leaders and employees of the company and the research literature the research done by using literature and writing that are closely related to the object of the research is intended to obtain a theoretical basis to be used in discussing the problem examined.The results showed that thetrend analysis which includes sales, net income and total assets increased from 2011 to 2014, for the sale of in 2011 increased by 1,28%, in 2012 to the year 2013 amounted to 1,46%, and the year 2013 to 2014 amounted to 1,56%. Net profit from the year 2011 to the year 2012 increased by 2,18%, in 2012 to the year 2013 amounted to 3,33% and in 2013 to 2014 amounted to 7,80%. Total assets from 2011 to 2012 increased by 1,50%, in 2012 to the year 2013 amounted to 2,28%, and in 2013 to 2014 amounted to 2,38%.